Distribution of primary sources for melon selection - Khakimov Rafiqjon; Halimova Mastura; Khusanov Bakhriddin; Anarbayev Jakhongir; Ko‘chimova Gulmira (BIO Web of Conferences)
The aim of the research was to select early maturing melon varieties of high quality and resistant to powdery mildew. In the nursery of the main resource for melon breeding for maturity, fruit weight, soluble dry matter content and resistance to powdery mildew, 28 cultivars of Russian, Italian, Dutch, Japanese and Chinese selections were isolated. The area of each sample in the nursery for the study of varietal samples is 10 m2, irretrievably. According to the early ripening of fruits stood out samples Holland No 101, No 102, Japan Earls verda Natsu, Yellow King, Russia No 1 and were 72–77 days. According to allocation by the content of soluble solids in fruits of samples Russia No 02, Holland No 101, China ECO-117, No 01, No 02, Japan Festa, Earls verda Natsu had an average content of soluble solids - 14.3–16.3%, the highest reached 18%. These samples are recommended for selection of varieties with high sugar content. The studied melon samples were 100% resistant to powdery mildew, and they can be used as donors in the selection of varieties resistant to the disease.